Incivilidade na educação superior - Cittolin, Simone Francescon (2014)
This research presents an investigation on successful teaching practices of academics related to student incivility in Higher Education. By analyzing such practices of some academics who work in federal, state and private institutions in the western side of Parana State, the research aimed to identify some principles that can guide academics' practice and assist them to address this phenomenon. With this purpose, we sought to first conduct a literature review on Higher Education in Brazil, presenting a brief history of this level of education in the country and how it is presented in the current context. Following, we discussed teaching in Higher Education covering the profile and the pedagogical training of these professionals, some necessary skills for teaching in Higher Education, and the importance of student-teacher ratio for greater efficiency in the higher education student learning. In continuation, we sought to understand the phenomenon of incivility, and as in the Brazilian context the issue has received little attention in the field of educational research, which is revealed by the absence of research on it at the Bank of Theses and Dissertations from CAPES, we looked for studies published in Canada, Kuwait, and especially in the United States. We highlight Appleby (1990), Amada (1992) Sorcinelli (1994), Boice (1996), Hanson (2000), Morissette (2001), Feldmann (2001), Jackson and Nilson (2004), and Hirschy Braxton (2004), Rudolph (2005), Clark (2007), Clark and Springer (2007), and Patron Bisping (2008), Bartels, Bucy and Nordstrom (2009), Marchand-Stenhoff (2009), Rehling and Bjorklund (2010), Alkandari (2011) and Williamson (2011), Black, Wygonik and Tony (2011), Marlow (2013), Thompson (2013), which revealed that incivility has increased, interfering with the teaching and learning process, thus compromising the welfare of the teacher, the students and the educational process as a whole. It is proposed, in this review, to explore the general concept of incivility in Education, then to deepen their meanings in the context of Higher Education. We chose to use the concept of Feldmann (2001), to guide this dissertation, who understands incivility as "any action that interferes with the harmonious environment and cooperative learning in the classroom" (p. 137). The implications of the manifestations of incivility in the proposed framework and the factors that contribute to this phenomenon are also discussed, as well as some promising educational practices for addressing expressions of incivility in Higher Education. The fieldwork, conducted under a qualitative approach, combines the application of a questionnaire to 30 academics that, according to some criteria, use successful practices to address expressions of incivility, and semi-structured interviews with 7 academics selected through the questionnaire. The content of the interviews was subjected to a content analysis, according to Bardin (2002), through which, then, it was possible to identify some principles that can guide the pedagogical practice of academics and help them address the phenomenon of incivility in Higher Education.